Comparing Estimates of Fall-Related Mortality Incidence Among Older Adults in the United States. (25th October 2018) - Lohman, Matthew C; Sonnega, Amanda J; Nicklett, Emily J; Estenson, Lillian; Leggett, Amanda N
Abstract: Background: Falls are the leading cause of injury-related mortality among older adults in the United States, but incidence and risk factors for fall-related mortality remain poorly understood. This study compared fall-related mortality incidence rate estimates from a nationally representative cohort with those from a national vital record database and identified correlates of fall-related mortality. Methods: Cause-of-death data from the National Death Index (NDI; 1999–2011) were linked with eight waves from the Health and Retirement Study (HRS), a representative cohort of U.S. older adults ( N = 20, 639). Weighted fall-related mortality incidence rates were calculated and compared with estimates from the Centers for Disease Control and Prevention (CDC) vital record data. Fall-related deaths were identified using International Classification of Diseases (Version 10) codes. Person-time at risk was calculated from HRS entry until death or censoring. Cox proportional hazards models were used to identify individual-level factors associated with fall-related deaths. Results: The overall incidence rate of fall-related mortality was greater in HRS–NDI data (51.6 deaths per 100, 000; 95% confidence interval: 42.04, 63.37) compared with CDC data (42.00 deaths per 100, 000; 95% confidence interval: 41.80, 42.19). Estimated differences between the two data sources were greater for men and adults aged 85 years and older. Greater age, male gender, and self-reported fall history were identified as independent risk factors for fall-related mortality. Conclusion: Incidence rates based on aggregate vital records may substantially underestimate the occurrence of and risk for fall-related mortality differentially in men, minorities, and relatively younger adults. Cohort-based estimates of individual fall-related mortality risk are important supplements to vital record estimates.